2011
DOI: 10.1021/ja206818n
|View full text |Cite
|
Sign up to set email alerts
|

Selective Polycarboxylation of Semiconducting Single-Walled Carbon Nanotubes by Reductive Sidewall Functionalization

Abstract: The efficient and controllable synthesis, the detailed characterization, and the chemical postfunctionalization of polycarboxylated single-walled carbon nanotubes SWCNT(COOH)(n) are reported. This innovative covalent sidewall functionalization method is characterized by (a) the preservation of the integrity of the entire σ-framework of SWCNTs; (b) the possibility of achieving very high degrees of addition; (c) control of the functionalization degrees by the variation of the reaction conditions (reaction time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 84 publications
2
65
0
6
Order By: Relevance
“…Metallic tubes were also reported preferentially etched away by water and methane plasma because of their higher reactivity (13,14). On the other hand, H 2 O 2 (15), azomethineylides (16), and gaseous SO 3 (17) preferentially attacked s-SWCNTs, and recently s-SWCNTs were also shown to be preferentially polycarboxylated via reductive sidewall functionalization (18). However, it has not been studied yet if confinement of metal cluster catalysts within metallic and semiconducting SWCNTs affects chemical reactions differently.…”
mentioning
confidence: 99%
“…Metallic tubes were also reported preferentially etched away by water and methane plasma because of their higher reactivity (13,14). On the other hand, H 2 O 2 (15), azomethineylides (16), and gaseous SO 3 (17) preferentially attacked s-SWCNTs, and recently s-SWCNTs were also shown to be preferentially polycarboxylated via reductive sidewall functionalization (18). However, it has not been studied yet if confinement of metal cluster catalysts within metallic and semiconducting SWCNTs affects chemical reactions differently.…”
mentioning
confidence: 99%
“…While comparing the position of the bands in the G-region shows that for the spectra recorded at 532 and 632 nm shows a shift of ≤5 cm Studies by Mevellec et al and Gebhardt et al showed in the Raman studies (noting these studies were Raman not SERS studies) that SWCNTs with covalently functionalized chemical groups attached showed changes in RBM frequencies and transition energies dependent upon the both the size of the side group and also the chemical nature of the side group e.g. when oxygen atoms lie close to the tubes a larger shift in transition energy occurs as compared to that of other carbonaceous chains [34,42]. Mevellec et al [34] reported a blueshift of RBM frequencies for carbon based moieties (example SWCNT-(CH 2 ) 11 -R) compared to oxygenated moieties (example SWCNT-CO 2 (-R)) of c.a.…”
Section: Resultsmentioning
confidence: 99%
“…3 mg of HiPco SWCNTs (batch n. HP27-078) were dispersed in 5 ml milliQ H 2 O with the assistance of sonication (30 min). The two solutions were mixed and the resulting suspension was sonicated for further 30 centrifuged at 1000 rpm for 1 h. A fraction (70%) of the supernatant solution was collected and directly used for the absorption and emission measurements. A fraction of the solution was deposited by spin coating on SiO 2 surface for Raman spectroscopy characterization.…”
Section: Ndi1mentioning
confidence: 99%